Innovation on Development Minimum Essential Forces Policy of the Indonesia Armed Forces - Sudarminto, Heru; Hadna, Agus Heruanto; Darwin, Muhadjir; Kutanegara, Pande Made (Global Writing Academica Researching and Publishing, 2024)
Policy on military posture development is a vital element of defense forces policy, which contains of national commitment to allocate all resources to build military strength and capabilities. Every country has unique military posture development policy, which is differ one to other due to its perception of threats and strive for its nation’s interests. Indonesia enacted the policy of minimum essential forces (KPM TNI) of Indonesia armed forces to safeguarding the sovereignty and territorial integrity of Indonesia. The KPM TNI is targeting to have capabilities to handle two trouble spots at the same time caused by invasion of foreign armed forces or domestic rebellion. The KPM TNI policy has started in 2010 and should be finish in 2024. But, after two decades of its implementation the progress of the KPM TNI policy is fall behind schedule. For that reason, this research is aimed to find out the main factors that hampers the progress of the KPM TNI Policy. By doing it, hopefully able to recommend the best alternative to expedite the KPM TNI Policy to achieve the target within remaining time.